Meningkatkan Keterampilan Memecahkan Masalah Matematika Menggunakan Kombinasi Model PBL, NHT, dan Permainan ULTRASI - Nor Hafizah; Wahdah Refia Rafianti (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The selection of suitable instructional models significantly contributes to raising the quality of learning interactions between teachers and students. The present classroom-based action research was implemented with fifth-grade students at SDN Kertak Hanyar 1–3, Banjar Regency, to evaluate the impact of implementing Problem-Based Learning, Numbered Heads Together, and the ULTRASI game on learning activities, problem-solving skill, and mathematics achievement in the topic of "Angles." Data were collected through assessments of problem-solving skills, observations of the learning process, and both individual and group written tests. The findings revealed that all three instructional models effectively improved student participation, problem-solving skills, and academic performance. PBL supported students in developing systematic approaches to problem-solving, NHT strengthened collaboration and group accountability, while ULTRASI enhanced conceptual understanding through engaging and visually appealing media. The successful implementation of these strategies was evidenced by the achievement of predetermined performance indicators.